Validasi Eksperimental dan Teoritis Daya Dukung Tiang PVC dengan Metode Mazurkiewicz dan Mayerhof - Susy Srihandayani; Azwan Azis; Wan Ramli (Jurnal Karajata Engineering, 2025)
Development in areas with soft soil conditions, such as Dumai, faces technical challenges related to low carrying capacity and high land subsidence. Lightweight and economical foundation solutions are an urgent need, especially for small and medium-scale structures. This study aims to validate the axial bearing capacity of PVC poles in soft clay soils using two approaches: the experimental interpretation of the Mazurkiewicz method and the theoretical approach of the Meyerhof method. Laboratory tests were performed on four variations of PVC pipe diameters (2", 2.5", 3", and 4") planted vertically in saturated soft soil. The load-drop data were analysed using the Mazurkiewicz method, while the theoretical calculation of the bearing capacity was based on the soil parameters of the direct shear test and the Atterberg limit. The results showed that the ultimate capacity value of the Mazurkiewicz method was slightly higher than that of the Meyerhof method, with a difference of 0.11% to 3.53%. This difference is due to the contribution of buoyancy forces from the trapped air in the closed pipe and the increased lateral friction due to the flexibility of the PVC material. This study confirms the potential of PVC poles as a lightweight and economical foundation solution in soft soils, as well as the relevance of the Mazurkiewicz method as a complement to the classical method.